DEVELOPING RABBIT FARMING AS AN ALTERNATIVE INCOME SOURCE: EDUCATING THE COMMUNITY ON ECONOMIC VALUE AND HEALTH BENEFITS - Prihantini Prihantini; Ai Rukmini; Ni Made Rianita; Lenni Lukitasari; Hikmah Sekarningtyas (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Facing economic challenges resulting from dependence on the agricultural sector and informal employment with fluctuating incomes, this situation demands the presence of alternative, easily implemented productive businesses, one of which is rabbit farming, which has high economic and health value. This Community Service Program (PKM) activity aims to increase public understanding regarding the economic potential and health benefits of rabbit meat, provide technical cultivation skills, and encourage the establishment of household-scale rabbit farming businesses. The problem formulation includes low economic literacy, minimal technical skills, and a lack of public understanding of rabbit market opportunities. The methods used include initial observation, counseling, technical training, business mentoring, and evaluation through pre-tests, post-tests, practical observations, and participatory interviews. The results of the activity showed a significant increase in economic and health literacy, where public understanding of the economic potential of rabbits increased from 23% to 87%, and knowledge of health benefits increased from 31% to 82%. The technical training also increased participant competency by 62%. Seventy-two percent of participants expressed their readiness to start a rabbit farming business, with the potential for additional income of Rp 350,000–1,650,000 per month. In conclusion, this Community Service Program (PKM) effectively increased the community's knowledge, skills, and entrepreneurial motivation. The program's sustainability requires continued mentoring and village institutional support to strengthen livestock groups and expand market access.